Enriching the Islamic tradition in research inquiry: some practical guidelines in using qualitative data collection techniques. - Ariffin, Adlina (InThought, 2021)
Due to the huge interest for qualitative data, a thorough understanding on the implementation of the qualitative data collection techniques is indeed paramount. Hence, the fundamental intention of this book is to assist social researchers especially postgraduate students and novice researchers who are interested to conduct their research qualitatively. One unique feature of the book is that it accentuates and connects each data collection technique to the Islamic tradition as entrenched in the Quran and Sunnah